Evaluation of Microwave Absorption Performance of Annealed Cr2AlC at Different Temperatures. (1st October 2022) - Guo, Yang; Song, Yuyang; Wen, Jin; Yan, Zongkai; Zhang, Li; Zhang, Yin; Lu, Haipeng; Liang, Difei
Abstract : Cr2 AlC (CAC) has attracted increasing attention due to high conductivity and excellent oxidation resistance, which is useful for high-temperature microwave absorption. However, systematic research on microwave absorption performance of CAC at high temperatures is still lacking. In this work, CAC was synthesized by salt bath method followed by annealing at 500 °C–950 °C. Effects of various annealing temperatures on compositions and electromagnetic properties were studied. Results revealed slight oxidation of CAC at annealing temperature of 500 °C, with formation of small amounts of Al2 O3 and Cr2 O3 on the surface. Increase in annealing temperature to 950 °C generated Al2 O3 and Cr2 O3 components in CAC. CAC annealed at 500 °C showed better microwave absorption properties than annealed at 950 °C and pure CAC. Effective absorption bandwidth (Reflection loss, RL < −10 dB) of CAC annealed at 500 °C was estimated to 2.3 GHz (9.7–12.0 GHz), and RLmin was −28.1 dB with thickness of 2.0 mm. The reason for this had to do with appropriate micro-oxidation, which could increase the permittivity of CAC and enhance dielectric loss capability for electromagnetic waves. In sum, these findings look promising to have referential significance for the application and promotion of CAC in the field of high temperature microwave absorption.